Desire, Familiarity, and Engagement in Polyamory: Results From a National Sample of Single Adults in the United States - Moors, Amy C.; Gesselman, Amanda N.; Garcia, Justin R. (Frontiers in Psychology, 2021)
Intimacy and forming a family are hallmarks of marriage and family science. Recent national surveys in the U.S. and Canada have found that consensually non-monogamous relationships are common, though prevalence of specific types of consensual non-monogamy are unknown. The present research draws on a U.S. Census based quota sample of single adults (N = 3,438) to estimate the prevalence of desire for, familiarity with, and engagement in polyamory—a distinct type of consensually non-monogamous relationship where people typically engage in romantic love and sexual intimacy with multiple partners. Results show that 1 out of 6 people (16.8%) desire to engage in polyamory, and 1 out of 9 people (10.7%) have engaged in polyamory at some point during their life. Approximately 1 out of 15 people (6.5%) reported that they knew someone who has been or is currently engaged in polyamory. Among participants who were not personally interested in polyamory, 1 out of 7 (14.2%) indicated that they respect people who engage in polyamory. Few sociodemographic correlates emerged; no differences in prevalence were found based on political affiliation, income, religion, geographic region, or race/ethnicity. Sexual minorities, men, and younger adults reported greater desire to engage in polyamory (compared to heterosexuals, women, and older adults, respectively). Men and people with lower education backgrounds were more likely to have previously engaged in polyamory (compared to women and people with higher education backgrounds, respectively). Given that emotional and sexual intimacy is an important part of most people’s lives, understanding the varied ways in which people navigate their intimate lives is critical for the fields of relationship, sexuality, and family science.